Motor Clusters Reveal Differences in Risk for Psychosis, Cognitive Functioning, and Thalamocortical Connectivity: Evidence for Vulnerability Subtypes. (September 2018) - Dean, Derek J.; Walther, Sebastian; Bernard, Jessica A.; Mittal, Vijay A.
Abnormal development of parallel cortical-striatal networks may contribute to abnormal motor, cognitive, and affective behavior prior to the onset of psychosis. Partitioning individuals at clinical high risk (CHR) using motor behavior may provide a novel perspective on different etiological pathways or patient subtypes. A k -means cluster analysis was conducted in CHR ( N = 69; 42% female, mean age = 18.67 years) young adults using theoretically distinct measures of motor behavior. The resulting subtypes were then compared on positive and negative symptoms at baseline, and 2-year risk of psychosis conversion. CHR participants were followed for 2 years to determine conversion to psychosis. CHR subtypes and healthy controls ( n = 61; 57% female, mean age = 18.58 years) were compared on multiple cognitive domains and cortical-striatal connectivity. Results suggest 3 vulnerability subtypes of CHR individuals with different profiles of motor performance, symptoms, risk for conversion to psychosis, cognition, and thalamocortical connectivity. This approach may reflect a novel strategy for promoting tailored risk assessment as well as future research developing individualized medicine.